RECONCEPTUALIZACIÓN A LA TICA: APUNTES HISTÓRICOS PARA EL TRABAJO SOCIAL COSTARRICENSE - Villalobos Morales, Manuel Antonio (2018)
This article tries to reveal, from a historical materialist study, the conditions that allowed the outbreak of reconceptualization´s stage process in Costa Rica. Therefore, in a very synthetic way it rescues mediation of various kinds that affected the movement feat. These range from the Latin American and national conditions of greater historical scope to academic political mediations, which means that this process occurred in the seventies.